2021
DOI: 10.1080/14786419.2021.1999947
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and antibacterial depsidones from the endophytic fungus Chaetomium brasiliense isolated from Thai rice

Abstract: Four new depsidones, mollicellins V-Y (1-4), together with eight known depsidones (5-12) were isolated from the endophytic fungus, Chaetomium brasiliense, detached from stems of Thai rice.Their structures were determined by extensive spectroscopic methods. Mollicellins X, H, and F (3, 8 and 10) showed potent cytotoxicity against the human oral epidermoid carcinoma (KB) cell line, and mollicellin F (10) also showed a potent cytotoxicity against the human hepatocellular carcinoma (HepG2) cell line. Besides, moll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Compounds 92 – 95 , 108 , and 109 had powerful antibacterial potential against Bacillus subtilis and Bacillus cereus (MICs 2.0–8.0 μg/mL) which was close to kanamycin (MICs 2.0 μg/mL), however, they displayed moderate efficacy on S. aureus ATCC25923 (MICs 16.0–64.0 μg/mL). Besides, 91 , 92 , 97 , 110 , and 111 were moderately active against different MRSA isolates (ATCC33591, ATCC33592, and ATCC43300, MICs 32.0–128.0 μg/mL) with the same MICs as oxacillin (MICs 32.0–128.0 μg/mL), whereas 91 and 92 also had moderate influence (MICs 32.0–128.0 μg/mL) against S. aureus SA1-3 clinical isolates ( Promgool et al, 2022 ). It was noted that C-4-CHO and complete lactone ring were significant for antibacterial potential against Gram-positive bacteria ( Promgool et al, 2022 ).…”
Section: Bioactivities Of Depsidonesmentioning
confidence: 99%
See 3 more Smart Citations
“…Compounds 92 – 95 , 108 , and 109 had powerful antibacterial potential against Bacillus subtilis and Bacillus cereus (MICs 2.0–8.0 μg/mL) which was close to kanamycin (MICs 2.0 μg/mL), however, they displayed moderate efficacy on S. aureus ATCC25923 (MICs 16.0–64.0 μg/mL). Besides, 91 , 92 , 97 , 110 , and 111 were moderately active against different MRSA isolates (ATCC33591, ATCC33592, and ATCC43300, MICs 32.0–128.0 μg/mL) with the same MICs as oxacillin (MICs 32.0–128.0 μg/mL), whereas 91 and 92 also had moderate influence (MICs 32.0–128.0 μg/mL) against S. aureus SA1-3 clinical isolates ( Promgool et al, 2022 ). It was noted that C-4-CHO and complete lactone ring were significant for antibacterial potential against Gram-positive bacteria ( Promgool et al, 2022 ).…”
Section: Bioactivities Of Depsidonesmentioning
confidence: 99%
“…Besides, 91 , 92 , 97 , 110 , and 111 were moderately active against different MRSA isolates (ATCC33591, ATCC33592, and ATCC43300, MICs 32.0–128.0 μg/mL) with the same MICs as oxacillin (MICs 32.0–128.0 μg/mL), whereas 91 and 92 also had moderate influence (MICs 32.0–128.0 μg/mL) against S. aureus SA1-3 clinical isolates ( Promgool et al, 2022 ). It was noted that C-4-CHO and complete lactone ring were significant for antibacterial potential against Gram-positive bacteria ( Promgool et al, 2022 ).…”
Section: Bioactivities Of Depsidonesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mollicellins are a representative type of depsidones with an isopentenyl modification which are produced by the Chaetomiaceae family, and 25 mollicellins (mollicellins A–Y) have been discovered. , However, biosynthetic studies of mollicellins have rarely been reported. In this work, we report the production of the new mollicellins Z ( 9 ) and Z1 ( 10 ) in Aspergillus nidulans A1145 by heterologous expression of a depsidone-encoding BGC from Ovatospora sp.…”
mentioning
confidence: 99%